Mobile Phone Use in a Developing Country: A Malaysian Empirical Study - Heng, Paul Ping Yeow; Yuen, Yee Yen; Connolly, Regina (Taylor & Francis Group, 2008)
Mobile phone use in a developing country: A Malaysian empirical study